Analysis of the Relationship Between Admission Prices and Line-Ups Artist on Visitor Purchasing Decisions to Attend the Saranghaeyo Indonesia 2024 Music Festival - Farrah, Farrah; Jatmiko, Najwa; Heykal, Muhammad (Program Studi Hospitality dan Pariwisata, 2024)
The purpose of this study and research was made to determine and analyze the relationship that exists between the admission ticket price variable on visitor purchasing decisions at the K-Pop themed music festival event, namely Saranghaeyo Indonesia 2024, the relationship between the artist line-up variable on visitor purchasing decisions at the Saranghaeyo Indonesia 2024 music festival event, and the relationship between admission ticket prices and artist line-ups on visitor purchasing decisions at the Saranghaeyo Indonesia 2024 music festival event.Through data collection conducted by means of survey research. The participants in this study were visitors who attended the Saranghaeyo Indonesia 2024 event, and the sample selection was 100 respondents. The technique of collecting data using a questionnaire that has been tested for validity and reliability, and with data analysis techniques using multiple linear regression analysis. The study showed positive and significant results, as follows: (1) There is a positive influence of the admission ticket price on consumer purchasing decisions at the Saranghaeyo Indonesia 2024 event. This is evidenced by the T test value, and getting a t value of 8.034 with a significance value of 0.001 <0.05, and a regression coefficient value of 0.407. (2) There is a positive influence of the artist line-up on consumer purchasing decisions at the Saranghaeyo Indonesia 2024 event. This is evidenced by the T test value, and getting a t value of 10.685 with a significance value of 0.001 <0.05, and a regression coefficient value of 0.768. (3) There is a positive influence of the admission ticket price and artist line-up on consumer purchasing decisions at the Saranghaeyo Indonesia 2024 event. This is evidenced by the F test value, and obtained a calculated f value of 71,778 with a significance value of 0.001 <0.05